TPX / PBT composite release film and preparation method thereof

Through the electrospinning film composite technology of TPX and PBT materials and the method of adding thermally conductive microspheres, the problems of adhesion and insufficient temperature resistance of the polyester base film in high temperature environments have been solved, and the high resistance of the double-sided release film has been achieved. Mild thermal conductivity.

CN119329155AActive Publication Date: 2025-01-21SUZHOU CHENPENG ELECTRONIC NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411183290.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-21
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The existing polyester base films are prone to defects due to adhesion problems during production and use, and their temperature resistance is low, making it difficult to meet the needs in high-temperature environments.

Method used

A double-sided release film is prepared using TPX and PBT materials through electrospinning film composite technology. Spiny spherical silver/carbon nanotube/cellulose composite microspheres are added to improve thermal conductivity and demoulding properties, and SiC electrospun is added to the middle layer. Silk film to reduce heat shrinkage.

Benefits of technology

A TPX/PBT composite release film with excellent release effect on both sides has been achieved. It has high temperature resistance, good thermal conductivity and improved mold release, and is suitable for high temperature environments and fine circuit manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005012822560000101
    Figure BDA0005012822560000101
  • Figure BDA0005012822560000111
    Figure BDA0005012822560000111
  • Figure BDA0005012822560000112
    Figure BDA0005012822560000112
Patent Text Reader

Abstract

The invention provides a TPX / PBT composite release film, the release film comprises a TPX film layer and a PBT film layer, the TPX film layer and the PBT film layer are compounded through an electrostatic spinning film, the electrostatic spinning film is a SiC electrostatic spinning film with the porosity of 85-95%, the thickness of the electrostatic spinning film is 20-30 [mu] m, the thickness of the TPX film is 150-180 [mu] m, the thickness of the PBT film is 120-150 [mu] m, and the thickness of the TPX film is 20-30 [mu] m. And the TPX film layer and the PBT film layer contain whisker-shaped heat-conducting particles with different particle sizes or the same particle size. The double-layer composite TPX / PBT film is adopted, the release forces of the two sides of the two release films are different, and the double-sided release film can be used for a flexible printed circuit board, a polarizer protection film in the panel industry, a multi-layer ceramic capacitor and a carrier for production, processing and transfer of a laminated built-in antenna.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of release films, and in particular to a TPX / PBT composite release film and a preparation method thereof. Background Art

[0002] Release film, also known as peeling film, isolation film, separation film, adhesive barrier film, release film, film, plastic film, masking film, silicone oil film, silicone oil paper, anti-adhesive film, slip film, Tianna paper, release paper, silliconfilm, release film, release. Double-sided release film is a special type of release film with release properties on both sides. Polyester base film is often used as the base film of release film. It is usually made of polyester chips as the main raw material, melt extruded to obtain thick sheets, and then rolled up to obtain film after longitudinal and transverse stretching and heat setting. Since the polyester base film will have many problems due to the mutual adhesion between the base films during the rolling and slitting process of the production process, as well as the subsequent packaging, transportation, and use, a certain amount of anti-adhesion particles are usually added to the surface layer of the polyester base film. At present, the anti-adhesion particles in polyester are mainly inorganic anti-adhesion particles, generally one or more of silicon dioxide, calcium carbonate, barium sulfate, titanium oxide, mica, and kaolin are selected. At present, silicon dioxide synthesized by the gel method has become the first choice of anti-adhesion particles at this stage because of its low price and good anti-adhesion effect. The low temperature resistance of ordinary polyester base film will cause deformation after heating. In order to improve the temperature resistance of the base film, it is necessary to reduce the thermal shrinkage of the base film in the longitudinal and transverse directions. The traditional method is to increase the heat setting time of the base film, but at the same time it will bring about a reduction in the longitudinal and transverse strength of the base film, which is not conducive to subsequent processing and use. TPX release film, full name is thermoplastic polyolefin release film, is a high-performance thermoplastic plastic material, with its excellent physical properties, chemical stability and processing convenience, it is widely used in electronics, electrical, automotive, packaging and other fields. In particular, in the manufacturing process of semiconductor flexible circuit boards, TPX release film plays a vital role. TPX release film has good transparency, glossiness and mechanical strength. It has excellent heat resistance and can remain stable at higher temperatures. In the manufacture of flexible circuit boards, TPX release film is often used as a cover layer or substrate to protect the circuit from physical damage and environmental influences. Taking advantage of its thermoplastic characteristics, TPX release film can be laminated with other materials by hot pressing and other methods to form a multi-layer composite material. As electronic devices develop towards smaller size and flexibility, TPX release films are also being optimized to adapt to more sophisticated circuit designs and higher performance requirements; the long-term stability of materials and their performance in extreme environments remain the focus of research. In the present invention, TPX and PBT are combined to prepare a release film with release effects on both sides to meet the requirements of use under higher requirements. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a TPX / PBT composite release film, which has a release effect on both sides and has excellent temperature resistance.

[0004] Technical solution: A TPX / PBT composite release film, the release film includes a TPX film layer and a PBT film layer. Preferably, the TPX film and the PBT film are composited by an electrospinning film, the electrospinning film is a SiC electrospinning film with a porosity of 85-95%, and a thickness of 20-30um, the thickness of the TPX film is 150-180um, and the thickness of the PBT film is 120-150um, and the TPX film layer and the PBT film layer contain tentacle-shaped thermal conductive particles of different particle sizes or the same particle size. Preferably, the preparation method of the tentacle-shaped thermal conductive particles includes the following steps: S11. The cellulose was dissolved in a mixed solvent of sodium hydroxide, urea and water in a mass ratio of 7:12:81 to obtain a cellulose solution having a concentration of 5.2-6.5wt%; S12. The calcium carbonate and carbon nanotubes were added to the cellulose solution, the mass volume ratio of calcium carbonate, carbon nanotubes and cellulose solution was 2-4g:3.5-5g:100mL to obtain a mixed cellulose solution; S13. The mixed cellulose solution is divided into two parts, the mixed cellulose solution is used as the aqueous phase, and the two solutions are added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, respectively, and stirred at different or the same speeds, and 2-propylene oxide is added. After the reaction is completed, ethanol is added, and the cellulose microspheres of different or the same particle size are obtained by filtration and drying; S14. adding two cellulose microspheres of different or same particle sizes to a dilute hydrochloric acid solution, stirring the reaction, filtering and drying to obtain porous cellulose microspheres; S15. Add two porous cellulose microspheres of different or same particle sizes into an ethylene glycol solution containing PVP, mix and stir evenly, then dropwise add an ethylene glycol solution containing silver nitrate to react, and after the reaction is completed, filter to obtain spherical silver / carbon nanotube / cellulose composite microspheres of different particle sizes. Preferably, in step S13, the mixed cellulose solution is divided into two parts, and the mixed cellulose solution is used as the aqueous phase. The two solutions are respectively added dropwise into the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1200-1600r / min and a speed of 1500-1800r / min, respectively, and the volume ratio of the aqueous phase to the oil phase is 4-6:1. 2-propylene oxide is added, and ethanol is added after the reaction is completed. The mixture is filtered and dried to obtain two cellulose microspheres with different or same particle sizes. Preferably, in step S15, the mass volume ratio of the porous cellulose microspheres, PVP, silver nitrate and ethylene glycol is 20-30 g: 1-2 g: 3-6 g: 200-300 mL. The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. Add two different or same particle sizes of thorny silver / carbon nanotube / fiber microspheres to TPX and PBT, respectively, mix well, add to a twin-screw extruder for granulation, and prepare modified TPX particles and PBT particles; S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain TPX films and PBT films; S3. The three layers of TPX membrane, SiC electrospun membrane and PBT membrane are stacked in sequence, and the SiC electrospun membrane is heated and then pressurized to obtain a TPX / PBT composite release film. Preferably, in step S1, the mass ratio of the spherical silver / carbon nanotube / fiber microspheres to TPX is 0.2-0.5:10, and the mass ratio of the spherical silver / carbon nanotube / fiber microspheres to PBT is 0.2-0.4:10. Preferably, in step S3, the SiC electrospinning membrane is heated to a temperature of 220-250°C and the pressurized pressure is 4-8 N / cm 2 Beneficial effects: The TPX / PBT composite release film of the present invention has the following advantages: 1. The present invention adopts a double-layer composite TPX / PBT film, and the release forces on both sides of the two release films are different. The double-sided release film can be used for flexible printed circuit boards, polarizer protective films in the panel industry, multilayer ceramic capacitors, and carriers for the production, processing and transfer of laminated built-in antennas, etc.; 2. The release film provided by the present invention contains spiky silver / carbon nanotube / fiber microspheres, which can play a dual role. First, the microspheres can form slight protrusions on the surface layer of the release film, which can reduce the contact area between the release film and other contact parts, thereby improving its demoulding performance. At the same time, it also has a good release effect under high temperature conditions, and microspheres of different particle sizes can be designed to meet the requirements under different use conditions; second, the microspheres contain carbon nanotubes and nanosilver tentacles, which can form a heat conduction path in the release film, thereby improving the heat conduction effect of the release film; 3. In the present invention, a SiC film prepared by electrospinning is added between the two release films, so that the base film obtained under the same processing conditions has a lower thermal shrinkage rate, and the SiC film increases the thermal conductivity of the release film. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 The preparation method of tentacle-shaped thermally conductive particles comprises the following steps: S11. The cellulose was dissolved in a mixed solvent of sodium hydroxide, urea and water in a mass ratio of 7:12:81 to obtain a cellulose solution having a concentration of 5.2wt%; S12. The calcium carbonate and carbon nanotubes were added to the cellulose solution, the mass volume ratio of calcium carbonate, carbon nanotubes and cellulose solution was 2g:3.5g:100mL to obtain a mixed cellulose solution; S13. The mixed cellulose solution was divided into two parts, and the mixed cellulose solution was used as the aqueous phase. The two solutions were respectively added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1200 r / min and 1600 r / min, respectively, with the volume ratio of the aqueous phase to the oil phase being 4:1, and 2-propylene oxide was added. After the reaction was completed, ethanol was added, and the mixture was filtered and dried to obtain cellulose microspheres of two different particle sizes; S14. Add two cellulose microspheres of different particle sizes to a 0.1 mol / L dilute hydrochloric acid solution, stir to react, filter and dry to obtain porous cellulose microspheres; S15. Add two porous cellulose microspheres of different or same particle sizes into an ethylene glycol solution containing PVP, mix and stir evenly, then dropwise add an ethylene glycol solution containing silver nitrate to react. The mass volume ratio of the porous cellulose microspheres, PVP, silver nitrate and ethylene glycol is 20g:1g:3g:200mL. After the reaction is completed, filter to obtain thorny silver / carbon nanotube / cellulose composite microspheres of different particle sizes. Example 2 The preparation method of tentacle-shaped thermally conductive particles comprises the following steps: S11. The cellulose was dissolved in a mixed solvent of sodium hydroxide, urea and water in a mass ratio of 7:12:81 to obtain a cellulose solution having a concentration of 6.5wt%; S12. The calcium carbonate and carbon nanotubes were added to the cellulose solution, the mass volume ratio of calcium carbonate, carbon nanotubes and cellulose solution was 4g:5g:100mL to obtain a mixed cellulose solution; S13. The mixed cellulose solution was divided into two parts, and the mixed cellulose solution was used as the aqueous phase. The two solutions were respectively added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1500 r / min and a speed of 1800 r / min, respectively, with the volume ratio of the aqueous phase to the oil phase being 6:1, and 2-propylene oxide was added. After the reaction was completed, ethanol was added, and the mixture was filtered and dried to obtain cellulose microspheres of two different particle sizes; S14. Add two cellulose microspheres of different particle sizes to a 0.1 mol / L dilute hydrochloric acid solution, stir to react, filter and dry to obtain porous cellulose microspheres; S15. Add two porous cellulose microspheres of different or same particle sizes into an ethylene glycol solution containing PVP, mix and stir evenly, then dropwise add an ethylene glycol solution containing silver nitrate to react. The mass volume ratio of the porous cellulose microspheres, PVP, silver nitrate and ethylene glycol is 30g:2g:6g:300mL. After the reaction is completed, filter to obtain thorny silver / carbon nanotube / cellulose composite microspheres of different particle sizes. Example 3 The method for preparing the tentacle-shaped thermally conductive particles comprises the following steps: S11. The cellulose was dissolved in a mixed solvent of sodium hydroxide, urea and water in a mass ratio of 7:12:81 to obtain a cellulose solution having a concentration of 6 wt %; S12. The calcium carbonate and carbon nanotubes were added to the cellulose solution, the mass volume ratio of calcium carbonate, carbon nanotubes and cellulose solution was 3g:4g:100mL to obtain a mixed cellulose solution; S13. The mixed cellulose solution was divided into two parts, and the mixed cellulose solution was used as the aqueous phase. The two solutions were respectively added dropwise into the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1200 r / min and a speed of 1600 r / min, respectively, with the volume ratio of the aqueous phase to the oil phase being 5:1, and 2-propylene oxide was added. After the reaction was completed, ethanol was added, and the mixture was filtered and dried to obtain two cellulose microspheres with different particle sizes, which were respectively recorded as MCBs-1 and MCB-2; S14. adding two cellulose microspheres of different or same particle sizes to a dilute hydrochloric acid solution, stirring the reaction, filtering and drying to obtain porous cellulose microspheres; S15. Add two porous cellulose microspheres of different or same particle sizes into an ethylene glycol solution containing PVP, mix and stir evenly, then add dropwise an ethylene glycol solution containing silver nitrate to react, the mass volume ratio of porous cellulose microspheres, PVP, silver nitrate and ethylene glycol is 25g:1.5g:5g:240mL. After the reaction is completed, filter to obtain thorny silver / carbon nanotube / cellulose composite microspheres of different particle sizes, and record the two thorny silver / carbon nanotube / cellulose composite microspheres of different particle sizes as Ag-MCBs-1 and Ag-MCB-2, respectively. Example 4 The difference between Example 4 and Example 3 is that the stirring speed in step 13 is different. In step S13: the mixed cellulose solution is divided into two parts, the mixed cellulose solution is used as the water phase, and the two solutions are respectively added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1300 r / min and a speed of 1680 r / min, respectively, the volume ratio of the water phase to the oil phase is 5:1, and 2-propylene oxide is added. After the reaction is completed, ethanol is added, and the mixture is filtered and dried to obtain two cellulose microspheres with different particle sizes. The two cellulose microspheres with different particle sizes are respectively recorded as MCBs-1 and MCB-2; In step S15: two spherical silver / carbon nanotube / cellulose composite microspheres with different particle sizes are respectively recorded as Ag-MCBs-1 and Ag-MCB-2. Example 5 The difference between Example 5 and Example 3 is that the stirring speed in step 13 is different. In step S13: the mixed cellulose solution is divided into two parts, the mixed cellulose solution is used as the water phase, and the two solutions are respectively added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1350 r / min and a speed of 1750 r / min, respectively, the volume ratio of the water phase to the oil phase is 5:1, and 2-propylene oxide is added. After the reaction is completed, ethanol is added, and the mixture is filtered and dried to obtain two cellulose microspheres with different particle sizes. The two cellulose microspheres with different particle sizes are respectively recorded as MCBs-1 and MCB-2; In step S15: two spherical silver / carbon nanotube / cellulose composite microspheres with different particle sizes are respectively recorded as Ag-MCBs-1 and Ag-MCB-2. Example 6 The difference between Example 6 and Example 3 is that the stirring speed in step 13 is different. In step S13: the mixed cellulose solution is divided into two parts, the mixed cellulose solution is used as the water phase, and the two solutions are respectively added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1500r / min and a speed of 1800r / min, respectively, the volume ratio of the water phase to the oil phase is 5:1, and 2-propylene oxide is added. After the reaction is completed, ethanol is added, and the cellulose microspheres with two different particle sizes are obtained by filtering and drying. The two cellulose microspheres with different particle sizes are respectively recorded as MCBs-1 and MCB-2; In step S15: two spherical silver / carbon nanotube / cellulose composite microspheres with different particle sizes are respectively recorded as Ag-MCBs-1 and Ag-MCB-2. Example 7 The difference between Example 6 and Example 3 is that the stirring speed in step 13 is different. In step S13: the mixed cellulose solution is used as the aqueous phase, and the aqueous phase solution is added dropwise to the oil phase of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1600 r / min, the volume ratio of the aqueous phase to the oil phase is 5:1, and 2-propylene oxide is added. After the reaction is completed, ethanol is added, and cellulose microspheres are filtered and dried to obtain MCBs-1; In step S15: the particle size of the spherical silver / carbon nanotube / cellulose composite microspheres is recorded as Ag-MCBs-1. Table 1 shows the particle size of cellulose microspheres MCBs-1 particle size / um MCBs-2 particle size / um Example 3 75 44 Example 4 67 40 Example 5 62 36 Example 6 53 32 Example 7 43 / Table 2 shows the particle size of silver / carbon nanotube / cellulose composite microspheres Ag-MCBs-1 particle size / um Ag-MCBs-2 particle size / um Example 3 80 48 Example 4 71 46 Example 5 67 41 Example 6 59 36 Example 7 47 / Example 8 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrostatic spinning film, the electrostatic spinning film is a SiC electrostatic spinning film with a porosity of 85% and a thickness of 20 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The Ag-MCBs-1 prepared in Example 3 was added to TPX, and Ag-MCBs-2 was added to PBT. The mass ratio of Ag-MCBs-1 to TPX was 0.2:10, and the mass ratio of Ag-MCBs-2 to PBT was 0.2:10. After mixing, the mixture was added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles. S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 180um and a PBT film having a thickness of 150um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 220°C and then pressurized to form a composite membrane with a pressure of 4 N / cm 2 , and obtain the TPX / PBT composite release film. Example 9 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrostatic spinning film, the electrostatic spinning film is a SiC electrostatic spinning film with a porosity of 95% and a thickness of 30 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The Ag-MCBs-1 prepared in Example 4 was added to TPX, and Ag-MCBs-2 was added to PBT, the mass ratio of Ag-MCBs-1 to TPX was 0.3:10, and the mass ratio of Ag-MCBs-2 to PBT was 0.3:10. After mixing, the mixture was added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles; S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 170um and a PBT film having a thickness of 140um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 250°C and then pressurized to form a composite membrane with a pressure of 8 N / cm 2 , and obtain the TPX / PBT composite release film. Example 10 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrostatic spinning film, the electrostatic spinning film is a SiC electrostatic spinning film with a porosity of 85% and a thickness of 20 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The Ag-MCBs-1 prepared in Example 5 was added to TPX, and Ag-MCBs-2 was added to PBT. The mass ratio of Ag-MCBs-1 to TPX was 0.4:10, and the mass ratio of Ag-MCBs-2 to PBT was 0.3:10. After mixing, the mixture was added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles. S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 160um and a PBT film having a thickness of 130um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 230°C and then pressurized to form a composite film. The pressurization pressure was 6N / cm 2 , and obtain the TPX / PBT composite release film. Embodiment 11 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrospinning film, the electrospinning film is a SiC electrospinning film with a porosity of 90% and a thickness of 25 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The Ag-MCBs-1 prepared in Example 6 was added to TPX, and Ag-MCBs-2 was added to PBT. The mass ratio of Ag-MCBs-1 to TPX was 0.5:10, and the mass ratio of Ag-MCBs-2 to PBT was 0.4:10. After mixing, the mixture was added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles. S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 150um and a PBT film having a thickness of 120um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 230°C and then pressurized to form a composite film. The pressurization pressure was 6N / cm 2 , and obtain the TPX / PBT composite release film. Example 12 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrospinning film, the electrospinning film is a SiC electrospinning film with a porosity of 90% and a thickness of 25 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The Ag-MCBs-1 prepared in Example 7 was added to TP and PBT, the mass ratio of Ag-MCBs-1 to TPX was 0.5:10, the mass ratio of Ag-MCBs-1 to PBT was 0.4:10, and after mixing, a twin-screw extruder was added for granulation to prepare modified TPX particles and PBT particles; S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 150um and a PBT film having a thickness of 120um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 230°C and then pressurized to form a composite film. The pressurization pressure was 6N / cm 2 , and obtain the TPX / PBT composite release film. Comparative Example 1 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film being composited by hot pressing; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The Ag-MCBs-1 prepared in Example 6 was added to TPX, and Ag-MCBs-2 was added to PBT. The mass ratio of Ag-MCBs-1 to TPX was 0.5:10, and the mass ratio of Ag-MCBs-2 to PBT was 0.4:10. After mixing, the mixture was added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles. S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 150um and a PBT film having a thickness of 120um; S3. The TPX film and the PBT film are stacked in sequence and laminated by hot pressing at a temperature of 200°C and a pressure of 6N / cm 2 , and obtain the TPX / PBT composite release film. Comparative Example 2 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrospinning film, the electrospinning film is a SiC electrospinning film with a porosity of 90% and a thickness of 25 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The MCBs-1 prepared in Example 6 was added to TPX, and MCBs-2 was added to PBT. The mass ratio of MCBs-1 to TPX was 0.5:10, and the mass ratio of MCBs-2 to PBT was 0.4:10. After mixing, the mixture was added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles. S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 150um and a PBT film having a thickness of 120um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 230°C and then pressurized to form a composite film. The pressurization pressure was 6N / cm 2 , and obtain the TPX / PBT composite release film. Comparative Example 3 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrospinning film, the electrospinning film is a SiC electrospinning film with a porosity of 90% and a thickness of 25 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. Ag-MCBs were added to TPX and PBT, respectively, the mass ratio of Ag-MCBs to TPX was 0.5:10, the mass ratio of Ag-MCBs to PBT was 0.4:10, and after mixing, they were added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles; S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 150um and a PBT film having a thickness of 120um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 230°C and then pressurized to form a composite film. The pressurization pressure was 6N / cm 2 , and obtain the TPX / PBT composite release film; Wherein, the preparation method of the Ag-MCBs comprises the following steps: S11. The cellulose was dissolved in a mixed solvent of sodium hydroxide, urea and water in a mass ratio of 7:12:81 to obtain a cellulose solution having a concentration of 6 wt %; S12. adding calcium carbonate and carbon nanotubes to the cellulose solution, wherein the mass volume ratio of calcium carbonate, carbon nanotubes and cellulose solution is 3g:4g:100mL to obtain a mixed cellulose solution; S13. The mixed cellulose solution was used as the aqueous phase, and the aqueous phase solution was added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, respectively, and stirred at a speed of 500 r / min. The volume ratio of the aqueous phase to the oil phase was 5:1, and 2-propylene oxide was added. After the reaction was completed, ethanol was added, and the cellulose microspheres were filtered and dried to obtain MCBs; S14. adding the cellulose microspheres to the dilute hydrochloric acid solution, stirring the reaction, filtering and drying to obtain porous cellulose microspheres; S15. Add porous cellulose microspheres to an ethylene glycol solution containing PVP, mix and stir evenly, then dropwise add an ethylene glycol solution containing silver nitrate to react. The mass volume ratio of porous cellulose microspheres, PVP, silver nitrate and ethylene glycol is 25g:1.5g:5g:240mL. After the reaction is completed, filter to obtain spherical silver / carbon nanotube / cellulose composite microspheres, recorded as Ag-MCBs. Comparative Example 4 A TPX / PBT composite release film, the release film comprising a TPX film layer and a PBT film layer, the TPX film and the PBT film are composited by an electrospinning film, the electrospinning film is a SiC electrospinning film with a porosity of 90% and a thickness of 25 um; The preparation method of the above-mentioned TPX / PBT composite release film comprises the following steps: S1. The silver nanowires were added to TPX and PBT, respectively, the mass ratio of the silver nanowires to TPX was 0.5:10, and the mass ratio of the silver nanowires to PBT was 0.4:10. After mixing, the mixture was added to a twin-screw extruder for granulation to prepare modified TPX particles and PBT particles; S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain a TPX film having a thickness of 150um and a PBT film having a thickness of 120um; S3. The TPX membrane, SiC electrospun membrane and PBT membrane were stacked in sequence, and the SiC electrospun membrane was heated to 230°C and then pressurized to form a composite film. The pressurization pressure was 6N / cm 2 , and obtain the TPX / PBT composite release film; The method for preparing the nano silver wire comprises the following steps: The ethylene glycol solution of PVP was mixed and stirred evenly, and then the ethylene glycol solution containing silver nitrate was added dropwise for reaction. The mass volume ratio of PVP, silver nitrate and ethylene glycol was 1g:3g:100mL. After the reaction was completed, the nano silver wires were obtained by filtration. Performance characterization: Peel strength test: According to the test method in GB / T 2792-1998 "180° peel strength test method for pressure-sensitive adhesive tape", the double-sided optical tape is attached to the test steel plate for testing, and the stripping is performed at a test speed of 300mm / min. The test results are recorded; Heat shrinkage and heat resistance: According to GB / T 33377-2016, the longitudinal and transverse heat shrinkage rates were tested using a micrometer and a blast-type constant temperature drying oven. The test conditions were 150°C for 30 minutes. Three samples were tested in each direction and the average value was calculated. Table 3 Table 4 Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A TPX / PBT composite release film, characterized in that: The release film comprises a TPX film layer and a PBT film layer.

2. The TPX / PBT composite release film according to claim 1, characterized in that: The TPX membrane and the PBT membrane are composited by electrospinning membrane, the electrospinning membrane is a SiC electrospinning membrane with a porosity of 85-95% and a thickness of 20-30um, the thickness of the TPX membrane is 150-180um, the thickness of the PBT membrane is 120-150um, and the TPX membrane layer and the PBT membrane layer contain tentacle-shaped thermal conductive particles of different particle sizes or the same particle size.

3. The TPX / PBT composite release film according to claim 2, characterized in that: The method for preparing the tentacle-shaped thermally conductive particles comprises the following steps: S11. The cellulose was dissolved in a mixed solvent of sodium hydroxide, urea and water in a mass ratio of 7:12:81 to obtain a cellulose solution having a concentration of 5.2-6.5wt%; S12. The calcium carbonate and carbon nanotubes were added to the cellulose solution, the mass volume ratio of calcium carbonate, carbon nanotubes and cellulose solution was 2-4g:3.5-5g:100mL to obtain a mixed cellulose solution; S13. The mixed cellulose solution is divided into two parts, the mixed cellulose solution is used as the aqueous phase, and the two solutions are added dropwise to the oil phases of Tween 80, Span 80 and liquid paraffin, respectively, and stirred at different or the same speeds, and 2-propylene oxide is added. After the reaction is completed, ethanol is added, and the cellulose microspheres of different or the same particle size are obtained by filtration and drying; S14. adding two cellulose microspheres of different or same particle sizes to a dilute hydrochloric acid solution, stirring the reaction, filtering and drying to obtain porous cellulose microspheres; S15. Add two porous cellulose microspheres of different or same particle sizes into an ethylene glycol solution containing PVP, mix and stir evenly, then dropwise add an ethylene glycol solution containing silver nitrate to react, and after the reaction is completed, filter to obtain spherical silver / carbon nanotube / cellulose composite microspheres of different particle sizes.

4. The TPX / PBT composite release film according to claim 3, characterized in that: In step S13, the mixed cellulose solution is divided into two parts, and the mixed cellulose solution is used as the water phase. The two solutions are respectively added dropwise into the oil phases of Tween 80, Span 80 and liquid paraffin, and stirred at a speed of 1200-1600 r / min and a speed of 1500-1800 r / min, respectively, and the volume ratio of the water phase to the oil phase is 4-6:

1. 2-propylene oxide is added, and ethanol is added after the reaction is completed. The mixture is filtered and dried to obtain two cellulose microspheres with different or same particle sizes.

5. The TPX / PBT composite release film according to claim 3, characterized in that: In the step S15, the mass volume ratio of the porous cellulose microspheres, PVP, silver nitrate and ethylene glycol is 20-30 g: 1-2 g: 3-6 g: 200-300 mL.

6. The method for preparing the TPX / PBT composite release film according to claim 2, characterized in that: The following steps are involved: S1. Add two different or same particle sizes of thorny spherical silver / carbon nanotube / fiber microspheres to TPX and PBT, respectively, mix well, add to a twin-screw extruder for granulation, and prepare modified TPX particles and PBT particles; S2. The modified TPX particles and PBT particles were cast into films by a single-screw extruder to obtain TPX films and PBT films; S3. The three layers of TPX membrane, SiC electrospun membrane and PBT membrane are stacked in sequence, and the SiC electrospun membrane is heated and then pressurized to obtain a TPX / PBT composite release film.

7. The method for preparing the TPX / PBT composite release film according to claim 6, characterized in that: In the step S1, the mass ratio of the spherical silver / carbon nanotube / fiber microspheres to TPX is 0.2-0.5:10, and the mass ratio of the spherical silver / carbon nanotube / fiber microspheres to PBT is 0.2-0.4:

10.

8. The method for preparing the TPX / PBT composite release film according to claim 6, characterized in that: In step S3, the SiC electrospinning membrane is heated to a temperature of 220-250° C. and the pressurized pressure is 4-8 N / cm 2 .

Citation Information

Patent Citations

  • Release film

    CN109466124A

  • Preparation method of anti-corrosion heat-resistant TPX release film

    CN116284901A

  • High-temperature silicone-oil-free release film and preparation method thereof

    CN118478580A

  • Release film

    CN218463217U

  • Release film

    JP2016129980A